1997
DOI: 10.1590/s0100-879x1997000500013
|View full text |Cite
|
Sign up to set email alerts
|

Role of endothelium in angiotensin II formation by the rat aorta and mesenteric arterial bed

Abstract: We investigated the angiotensin II (Ang II)-generating system by analyzing the vasoconstrictor effect of Ang II, angiotensin I (Ang I), and tetradecapeptide (TDP) renin substrate in the absence and presence of inhibitors of the renin-angiotensin system in isolated rat aortic rings and mesenteric arterial beds with and without functional endothelium. Ang II, Ang I, and TDP elicited a dose-dependent vasoconstrictor effect in both vascular preparations that was completely blocked by the Ang II receptor antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
2
7
0
3
Order By: Relevance
“…However, endothelial removal did not alter the effects of AT 1 R blockade on vasoconstriction suggesting that the endothelium is not necessary for vascular Ang II formation. In agreement with these observations, Leite et al 49 found that endothelium-denuded mesenteric arteries were still able to produce Ang II.…”
Section: Arenas Et Al Tnf-␣ and Vascular Ang II In Estrogen Deficiencmentioning
confidence: 55%
“…However, endothelial removal did not alter the effects of AT 1 R blockade on vasoconstriction suggesting that the endothelium is not necessary for vascular Ang II formation. In agreement with these observations, Leite et al 49 found that endothelium-denuded mesenteric arteries were still able to produce Ang II.…”
Section: Arenas Et Al Tnf-␣ and Vascular Ang II In Estrogen Deficiencmentioning
confidence: 55%
“…Although AngII formation in rodents is primarily ACErelated (2), non-ACE-dependent AngII formation has also been observed in rat heart (34) and vasculature (35,36). Guo et al (36) demonstrated that chymase expression and chymostatininhibitable ACE activity were significantly increased in spontaneously hypertensive rats, suggesting a possible role for this enzyme in AngII formation in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that captopril does not completely block the synthesis of ANG II in endothelial cells (25,57) suggests the existence of non-ACE pathways for ANG II formation and raises the question as to whether ACE is the sole enzyme responsible for ANG II generation in endothelial cells. Indeed, the existence of alternative ANG II-forming pathways in the vascular wall has been reported (17,25,26,31,32,40,42,44,58,60,65).…”
mentioning
confidence: 99%